Simvastatin and Muscle: Zebrafish and Chicken Show that the Benefits are not Worth the Damage - Campos, Laise M.; Guapyassu, Livia; Gomes, Cyro; Midlej, Victor; Benchimol, Marlene; Mermelstein, Claudia; Costa, Manoel Luis (Frontiers in Cell and Developmental Biology, 2022)
Simvastatin is one of the most common medicines prescribed in the world to treat human hypercholesterolemia. Simvastatin acts through the inhibition of cholesterol synthesis. Unfortunately, simvastatin causes unwanted side effects on muscles, such as soreness, tiredness, or weakness. Therefore, to understand the mechanism of action of simvastatin, it is important to study its physiological and structural impacts in muscle in varied animal models. Here we report on the effects of simvastatin on two biological models: zebrafish embryos and chicken muscle culture. In the last years, our group and others showed that simvastatin treatment in zebrafish embryos reduces fish movements and induces major structural alterations in skeletal muscles. We also showed that simvastatin and membrane cholesterol depletion induce major changes in proliferation and differentiation of muscle cells in chick muscle cultures. Here, we review and discuss these observations considering reported data on the use of simvastatin as a potential therapy for Duchenne muscular dystrophy.